Alternative Methods of Estimating Potential Output and the Output Gap : An Application to Sweden - Saxena, Sweta; Cerra, Valerie (Washington, D.C. : International Monetary Fund, 2000)
This paper reviews a number of different methods that can be used to estimate potential output and the output gap. Measures of potential output and the output gap are useful to help identify the scope for sustainable noninflationary growth and to allow an assessment of the stance of macroeconomic policies. The paper then compares results from some of these methods to the case of Sweden, showing the range of estimates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet